PENDIDIKAN AGAMA ISLAM, INTERNALISASI NILAI-NILAI ANTI KORUPSI DAN PENCEGAHAN TINDAK PIDANA KORUPSI - Moh. Fadhil (IAIN Pontianak, 2019)
This paper will discuss Islamic Religious Education and internalization of anti-corruption values as the effort to prevent corruption. The effort to overcome corruption crime not only with prosecution and eradication, but also with prevention efforts. One of the prevention efforts is education. Therefore, it needs anti-corruption education model as the resistence efforts toward corruptive behavior and to internalize the value of morality. It has to do literatively to build anti-corruption view. The aim of this paper is to understand integration of anti-corruption values in Islamic Religious Education model. Furthermore, this paper also discusses transformation of Islamic Religious Education that integrating anti-corruption values as the prevention efforts of widespread corruptive behavior and to increase corruption perception index. In this case, Islamic Religious Education must be able to make a methodological transformation in terms of cognitive anti-corruption literacy in each learning activity to all those learners. Furthermore, by building an analysis of social symptoms and public issues with a research approach, it must be able to build public morality. The success of the concept will be able to internalize anti-corruption values and to increase corruption perception index in the world.